2019
DOI: 10.1002/jcph.1562
|View full text |Cite
|
Sign up to set email alerts
|

Dosing of Continuous Fentanyl Infusions in Obese Children: A Population Pharmacokinetic Analysis

Abstract: Differences in fentanyl pharmacokinetics (PK) between obese and nonobese adults have previously been reported; however, the impact of childhood obesity on fentanyl PK is relatively unknown. We developed a population pharmacokinetic (PopPK) model using opportunistically collected samples from a cohort of predominately obese children receiving fentanyl per the standard of care. Using a probability‐based approach, we evaluated the ability of different continuous infusion strategies to provide steady‐state concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 40 publications
3
16
0
Order By: Relevance
“…In fact, a fentanyl population PK model that evaluated 30 children with obesity found an inverse association between post hoc weightnormalized clearance values and obesity classification. 20 The weight-normalized volume of distribution decreased with obesity in alignment with these findings, which could be attributed to the higher body fat mass in children with versus without obesity. 20 Together, the differences in weight-normalized clearance and volume of distribution in children with and without obesity suggest that similar weight-based infusion regimens can result in higher fentanyl C ss in children with obesity.…”
Section: Discussionsupporting
confidence: 65%
“…In fact, a fentanyl population PK model that evaluated 30 children with obesity found an inverse association between post hoc weightnormalized clearance values and obesity classification. 20 The weight-normalized volume of distribution decreased with obesity in alignment with these findings, which could be attributed to the higher body fat mass in children with versus without obesity. 20 Together, the differences in weight-normalized clearance and volume of distribution in children with and without obesity suggest that similar weight-based infusion regimens can result in higher fentanyl C ss in children with obesity.…”
Section: Discussionsupporting
confidence: 65%
“…2 This sampling scheme has already been used in published analyses of fentanyl PKs in children. [3][4][5] These irregular, sparse, opportunistic sampling strategies were the original motivation for application of nonlinear mixed effects models toward population PK (PopPK) analyses 6 and we have used such samples to perform a fentanyl PopPK analysis in children. 7 This prior study was the largest reported pediatric cohort (N = 130) for a PopPK analysis of fentanyl to date but significant residual variability remained, unexplained by the model.…”
Section: Articlementioning
confidence: 99%
“…This research is particularly important in the light of the over-prescription of opioids in recent years, and thus, the spreading wave of opioid addiction worldwide. [4,[38][39][40][41][42][43]. The addition of Mg 2+ may help to adequately control opioid treatment by reducing consumption, and thus, reducing adverse events [11][12][13].…”
Section: Discussionmentioning
confidence: 99%